Population size and breeding success of the Scopoli’s Shearwater on Lampione Islet (Avocetta, 2024)
The islet of Lampione, located in the archipelago of the Pelagie islands (Sicily channel), is known to be the Italian southernmost breeding site for the Scopoli’s Shearwater Calonectris diomedea. So far, there was little information on the number of Shearwaters attending the islet and on the status of this breeding population. Therefore, during an eight-year study period, we determined the active nests used by the birds and assessed the annual breeding success of the population on a subset of study nests. Counts of the active nests and of the birds attending the rafts at sea revealed a breeding population of approx. 230 pairs, which makes the islet the fifth-largest breeding colony among the Italian islands. Breeding success on Lampione ranged from 39.7% and 70.8% and was about 30% lower compared to that measured in the nearby colony of Linosa. Breeding failure on Lampione in 2018 was mainly due to predation on chicks by Yellow-legged Gulls Larus michaellis, but predation was later reduced by improving the concealing of existing burrows and the construction of artificial nests. We also observed intraspecific competition for nest sites. Our findings show the importance of the islet of Lampione, and of the Pelagie archipelago, for the conservation of this species.
Keywords: Italy; Pelagie islands; breeding success; Scopoli’s Shearwater; Calonectris diomedea